Legal documentation in Islamic finance: the courts’ approach in reconciling contractual inconsistencies - Oseni, Umar Aimhanosi (2015)
One of the emerging challenges in the practice of Islamic banking and finance in the modern world relates to legal documentation. The practice of Islamic banking and finance is often subjected to the prevailing laws and regulations in a particular jurisdiction. Accordingly, there are situations where complex commercial agreements utilized in the Islamic finance industry create some contractual inconsistencies due to the number of contractual documents used in a single transaction. To this end, this paper examines the court’s approach in reconciling such contractual inconsistencies without jeopardizing the original philosophy underlying the contract. The study adopts a conceptual approach while utilizing content analysis for some samples of relevant Islamic finance contracts and case law. It is argued that striking a fair balance between the Sharī‘ah clause in the Master Agreement and the ‘hierarchy’ clause is paramount. Absolute reliance on the ‘hierarchy’ clause as held recently in CLP Holding v. Singh [2014] EWCA Civ 1103, might pose some potential Sharī‘ah-compliance issues in Islamic finance documentation. The paper concludes that if the hierarchy clause is fundamentally premised on Sharī‘ah compliance as the governing principle underlying the entire contract, the clause will be considered the first resort, and there would not be any last resort as opposed to the prevailing practice under the English law.